ISLAMIC ECONOMY PERSPECTIVE AGAINST MILLENNIAL GENERATION BEHAVIOR IN MATARAM CITY; COD ONLINE SHOP SYSTEM - Ilmiati, Yulinda Nur; Yasin, Muaidy; Rois, Ihsan (Universitas Islam Negeri Mataram, 2024)
Online sales often need to be more balanced between the ordered goods and the goods received by the consumer. Having COD is one of the solutions to the problem. In the Islamic economy, the acceptance of goods and payment is done at the same time. The study aims to identify and analyze the behaviour of Millennials in daring shopping with the Cash on the Delivery (COD) payment system, which is performed qualitatively using explanatory methods. The findings explain that the reviews of the people around heavily influence the perception of daring shopping with COD in the millennial generation and are also affected by certain factors, namely price, advertising, location, and lifestyle. The behaviour of the Millennial Generation in daring sales carried out with the Cash-on-delivery (COD) system, according to the Islamic economic perspective, has been appropriate due to the sale activities becoming more practical as well as time and cost-efficient. (COD). From the Islamic economic perspective, payment in Cash when goods are received can be regarded as a practice consistent with the principles of justice and caution.